2007
DOI: 10.1161/01.res.0000266976.89667.31
|View full text |Cite
|
Sign up to set email alerts
|

Human PON3, Effects Beyond the HDL

Abstract: T he article by Shih et al 1 in this issue of CirculationResearch is the first report of transgenic expression of human Paraoxonase 3 (PON3) in mice and its ability to decrease significantly atherosclerotic lesion formation and adiposity. These effects were, interestingly, observed only in male but not in female mice on either C57BL/6J or LDLR KO backgrounds. Noteworthy, no human or mouse PON3 were detected in mouse HDL and plasma and therefore the effects of human PON3 were derived from PON3 in the tissues, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Moreover, human PON3 is present on HDL particles and absent in macrophages while the opposite is true for mice [1, 27]. In general, it has been postulated that human PON3 exerts its (antiatherogenic) function rather inside than outside the cells [35, 73], similar to PON2 and likely different from PON1. Studies performed by Shih et al also revealed a role for PON3 in lipid metabolism that links to adiposity; intriguingly, this was gender-specific for yet unknown reasons [35].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Moreover, human PON3 is present on HDL particles and absent in macrophages while the opposite is true for mice [1, 27]. In general, it has been postulated that human PON3 exerts its (antiatherogenic) function rather inside than outside the cells [35, 73], similar to PON2 and likely different from PON1. Studies performed by Shih et al also revealed a role for PON3 in lipid metabolism that links to adiposity; intriguingly, this was gender-specific for yet unknown reasons [35].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…PON3 is mainly expressed in the liver, and exerts anti-inflammatory and anti-oxidative properties in cellular lever, namely in hepatocytes [9, 11, 12]. PON3 was reported as a more efficient inhibitor of oxidative stress than PON1 in rabbit serum [13].…”
Section: Discussionmentioning
confidence: 99%
“…PON1 is also synthesized in the liver and is secreted into the serum where it performs antioxidant and anti-inflammatory activities [10]. However, the similar protective activities of PON3 are thought to take place mainly at the cellular level, namely in hepatocytes [11, 12]. Moreover, rabbit serum PON3 has a significantly more pronounced antioxidant effect when compared with serum PON1 [13], and serum PON3 concentration is also associated with the severity of hepatic impairment in patients with chronic liver disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although this may suggest distinct physiological roles for each of them ( 19 ), much remains unknown. All members of the PON family display antioxidant properties ( 20 ) and are mainly synthesized by the liver; however, at least in rabbits and humans, only PON1 and PON3 are found in the serum in association with HDL, where they prevent the oxidative modifi cation of LDL.…”
Section: Stress Exercisementioning
confidence: 99%